Tanzania's story of change in nutrition: Political commitment, innovation and shrinking political space - te Lintelo, Dolf J.H.; Page, Pippa; Kaganda, Joyceline; Esau, Deborah (Elsevier, 2020)
In the past 15 years, Tanzania has made considerable progress in the fight against child undernutrition. This paper analyses in what respects an enabling environment for nutrition action in Tanzania has emerged. It critically investigates the nature of government political commitment and assesses the breadth and depth of a range of public policies, initiatives and actions within and across nutrition-specific and nutrition-sensitive sectors, and at the national, sub-national and community levels. It finds that Tanzania has undertaken substantial policy innovation and institutional development, carrying significant promise to accelerate nutrition improvements, provided they are accompanied by stronger domestic investments, and greater political space enabling communities to hold the government to account for its performance combating malnutrition.